Joseph Pryor papers - Pryor, Joseph
Journal kept in an almanac by Pryor. Entries relate to weather, crop reports, local politics, Society of Friends meetings, and genealogical information. Includes a typewritten transcript of selected entries.
Quaker living in the Philadelphia, Penn., area.
Collection material in English.
Keywords: Agriculture -- Pennsylvania; Society of Friends -- Pennsylvania; Weather; Pennsylvania -- Genealogy; Pennsylvania -- Politics and government; Quakers